Strategies for an HIV cure: progress and challenges - Wang, Fu Sheng; Zhang, Linqi; Douek, Daniel; McMichael, Andrew; Xu, Xiao-Ning; Lewin, Sharon R. (Nature immunology, 2018)
The ‘Strategies for an HIV Cure’ conference was held 27–28 April 2018 in Beijing, China, and was hosted by The People's Republic of China Ministry of Science and Technology and the Chinese Academy of Sciences.